2022
DOI: 10.1039/d2gc03022e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient biodiesel production from rice bran oil using magnetite immobilized-recombinant lipase from probiotic Bacillus licheniformis

Abstract: With increasingly stringent environmental regulations, the pursuit for sustainable energy warrants approaches that are benign-by-design. Lipases have been found to be potential biocatalysts for converting fatty acid esters into biodiesel,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Strikingly, new signals at 399.9 and 163.7 eV were observed that could be attributed to the characteristic N 1s and S 2p signals arising from lysozyme and thus ascertained the successful immobilization of the antimicrobial protein. [ 13,50,51 ] It can be noted that the surface chemical changes identified by XPS in both PCL films and ES fibers were identical.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Strikingly, new signals at 399.9 and 163.7 eV were observed that could be attributed to the characteristic N 1s and S 2p signals arising from lysozyme and thus ascertained the successful immobilization of the antimicrobial protein. [ 13,50,51 ] It can be noted that the surface chemical changes identified by XPS in both PCL films and ES fibers were identical.…”
Section: Resultsmentioning
confidence: 89%
“…The codon‐optimized lipase from B. licheniformis was produced in‐house using BL21(DE3)pLysS expression system, as reported in the previous work. [ 50 ] The gram‐negative and gram‐positive bacterial strains E. coli K12 (MTCC 1302) and S. aureus (MTCC 87), respectively, were procured from IMTECH, Chandigarh, India.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, biodiesel (fatty acid methyl esters, FAME) has been recognized as an appropriate alternative to fossil fuel owing to their renewability, biodegradability, and low emission profiles [3,4]. In general, biodiesel is derived by esterification/transesterification of free fatty acids (FFAs), plant oils, animal fats, waste cooking oils, and microalgae and triglyceride with short-chain alcohols in the presence of homogeneous/heterogeneous catalysts [5]. Although the usage of homogeneous catalysts can achieve a high percentage of conversion rates, it also causes some salient problems such as expensive separation stages and large amounts of chemical wastewater [6].…”
Section: Introductionmentioning
confidence: 99%
“…The field of DNA biotechnology has brought about a revolution in modern biology, with countless applications in various domains, including medicine, forensics, environmental studies, and agriculture. [1][2][3][4][5][6][7][8][9] A widely used approach in this field involves leveraging the chemical reactivity of DNA to produce modified or synthetic nucleotides, which can be used to power an array of cutting-edge technologies such as functional nanostructure assembly, molecular motors, logic gates, CRISPR-Cas9 and biosensors. [10][11][12][13][14][15] On a different note, boronate ester chemistry-arising due to the specific reactivity of boronic acid with 1,2-and 1,3-diols-has garnered considerable interest in the field of chemical biology due to its biocompatibility and distinctive reactivity.…”
mentioning
confidence: 99%